Professionalization of Agricultural Work in Benin (London Journal of Research In Science: Natural and Formal, 2023)
Food availability is influenced by the means of production. A decrease in production affects market prices. In Benin, food production is changing. This paper seeks to analyze the influence of professionalization of work, the use of new technologies and individualism on agricultural production. Two data sources are used: the National Agricultural Census core module and the Harmonized Framework based on the World Food Programme food security survey, the results of the 2021-2022 agricultural season, the caloric proxy, shocks, historical variations in agricultural production, agricultural commodity prices, access to drinking water and improved toilets, and the seasonal calendar. Contributing factors related to food availability and access influence food consumption and livelihoods. On farms, 81.6% of farms are part-time with 2/12 months for non-professionals and 7-8/12 months for professionals. Respectively 2.0%, 6.9% and 11.9% keep accounting, have access to credit and are affiliated in agricultural producers' organization.
Keywords: professionalization; farm work; farming; tools; productivity